Kajian Dimensi Community-based Tourism dalam Pengembangan Desa Wisata Sumberbulu - Dhiany Sukma Arum; Dwiningtyas Padmaningrum; Joko Winarno (AGRITEXTS: Journal of Agricultural Extension, 2022)
Tourism development is currently directed towards sustainable tourism development. Domestic tourist visits to tourist villages are still low due to the lack of promotion of tourist villages due to budget constraints and local people themselves who do not understand the existence of tourist villages. One of the tourism concepts that can be applied to utilize local communities in the area is to introduce the concept of community-based tourism (CBT). This study aims to analyze the economic, social, cultural, environmental and political aspects which are the dimensions of CBT in the development of Sumberbulu Tourism Village. The basic research method used qualitative methods through a descriptive analysis approach. The determination of the research location was carried out intentionally in the Sumberbulu Tourism Village, Karanganyar Regency. The informants used in this study were purposive and snowball. Validation of data with source triangulation techniques and triangulation techniques. Data analysis used interactive data analysis. The results of the study show that the dimensions of CBT applied by the Sumberbulu Tourism Village include economic, social, cultural, environmental and political dimensions. The economic dimension applied is in the form of development funds, job creation, income generation and joint ventures. The social dimensions applied are in the form of involving members in every aspect, developing community pride, developing a quality of life and a fair distribution of roles, strengthening organizations, and authorizing communities. The cultural dimension applied is in the form of respecting and maintaining cultural uniqueness, helping to develop learning about cultural exchange, respecting cultural differences and human dignity. The environmental dimension applied is in the form of a carrying capacity area, ensuring environmental sustainability. The political dimension applied is in the form of institutional consolidation, increasing participation, guaranteeing rights in natural resource management.